pH-responsive nanocapsules as smart coating for corrosion protection: A review - N. S., Mohamed; J., Alias; N. A., Johari; A., Zanurin (Springer, 2023)
A new generation of smart coating contain nano capsule that actively respond to changes in the local environment has triggered great interest among material researchers in the field of anti-corrosion. Many researchers reported that the preparation of pH-responsive nano capsules is usually applying unfriendly chemicals, a complex procedure and time-consuming, which remains as a great challenge for effective corrosion protections. This review presents, the achievement during the last 10 years in the field of pH-responsive nano-capsules, the formulation technique of such nano-capsule, testing and evaluation of the pH-responsive nano-capsule.